RETHINKING COMMUNICATIVE COMPETENCE IN MODERN LINGUISTICS: THEORY, PRACTISE, AND PEDAGOGICAL IMPLICATIONS - Karimova Ruxshona (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
In recent decades, communicative competence has become one of the central concepts in modern linguistics and language education. This paper revisits its theoretical foundations and examines how it is applied in contemporary teaching practices. Rather than viewing language learning as the acquisition of grammatical knowledge alone, the article emphasizes the importance of meaningful interaction and contextual language use. Particular attention is given to classroom practices, learner engagement, and digital technologies in shaping communicative ability. The paper also reflects on some practical challenges that students and teachers face in real learning environments.